Endovascular Repair Using Suture-Mediated Closure Devices and Balloon Tamponade following Inadvertent Subclavian Artery Catheterization with Large-Caliber Hemodialysis Catheter - Park, Taek Kyu (Korean Circ J, 2016)
Accidental subclavian artery cannulation is an uncommon but potentially serious complication of central venous catheterization. Removal of a catheter inadvertently placed in the subclavian artery can lead to substantial bleeding, as achieving hemostasis in this area through manual compression presents considerable difficulty. Additionally, surgical treatment might be unsuitable for high-risk patients due to comorbidities. Here, we report a case of an inadvertently-inserted 11.5-French hemodialysis catheter in the subclavian artery during internal jugular venous catheterization. We performed percutaneous closure of the subclavian artery using three 6-French Perclose Proglide® devices with a balloon tamponade in the proximal part of the subclavian artery. Closure was completed without embolic neurological complications.